Optimizing The Use Of Cloud Technology In Public Sector Management Control (Case Study Of E-Government In Bandung City) - Nadila Lastanti; Mohamad Djasuli (Eduvest - Journal of Universal Studies, 2024)
This research aims to explore and analyze the optimization of cloud technology usage in public sector management control, focusing on the implementation of e-government in Bandung City as a case study. The research method used is a qualitative case study, collecting data through in-depth interviews, observations, and related document analysis. The results indicate that the application of cloud technology has brought significant benefits, including increased efficiency, accessibility, and scalability of e-government services. However, challenges related to data security and technological infrastructure limitations were also identified. Based on these findings, recommendations are provided to strengthen infrastructure, train employees, establish partnerships with the private sector, and conduct regular evaluations to enhance the application of cloud technology in e-government management in Bandung City and the public sector in general. This research is expected to provide valuable insights for the development and optimization of e-government services in various governmental contexts.